2006
DOI: 10.1007/s11104-006-9144-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of post-harvest regulated deficit irrigation on carbohydrate and nitrogen partitioning, yield quality and vegetative growth of peach trees

Abstract: The aim of the present work was to evaluate the effects of regulated deficit irrigation (RDI) applied in the post-harvest stage of peach\ud trees. The 3-year trial was carried out in Italy (N 4020¢, E 1648¢) on mature peach plants (cv ‘‘Springcrest’’) trained to transverse Y. From bud break to harvest, irrigation was carried out by applying 100% ETc, while from harvest to early autumn, plants were separated into three groups and subjected to different irrigation treatments (100, 57 and 34% ETc). The decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 33 publications
4
54
0
5
Order By: Relevance
“…For peach trees, Marsal et al (2004Marsal et al ( , 2005 reported that minimum values of around -1.5 MPa at the end of Stage II are associated with detrimental effects on fruit size at harvest. Similar results were presented by Dichio et al (2007) in peach and by Marsal et al (2009) in cherry. There are references in the literature pointing out that the threshold limits of SWP are variable between crops, crop development stages, soil characteristics and fruit loads.…”
Section: Assessing Crop Water Stresssupporting
confidence: 88%
See 2 more Smart Citations
“…For peach trees, Marsal et al (2004Marsal et al ( , 2005 reported that minimum values of around -1.5 MPa at the end of Stage II are associated with detrimental effects on fruit size at harvest. Similar results were presented by Dichio et al (2007) in peach and by Marsal et al (2009) in cherry. There are references in the literature pointing out that the threshold limits of SWP are variable between crops, crop development stages, soil characteristics and fruit loads.…”
Section: Assessing Crop Water Stresssupporting
confidence: 88%
“…On the other hand, the discharge differences between the two controlled apricot cropping areas were not effectively corrected. Dichio et al (2007) concluded that the success of an RDI strategy heavily relies on the adequate design and management of drip irrigation systems. Our results indicate that, despite the manager's efforts, more control (flow meters, pressure regulators) would be required at the irrigation network in order to effectively regulate deficit irrigation in the orchard.…”
Section: Discharge Pressure and Uniformity Of The Irrigation Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Other favorable results with this technique were obtained in studies developed by GIRONA et al (1993), in peach; by DOMINGO et al (1996), in real lemon; by DICHIO et al (2007) andLOPEZ et al (2008), in pear; by PEREZ-PEREZ et al (2009), in sweet orange;and GIJÓN et al (2009), in pistachios. Not as favorable result was found by GONZÁLEZ- ALTOZANO & CASTEL (2000) by applying the technique in tangerines, where a deficit of 50% of ETc, applied at the initial stage, achieved water savings of up to 23%, without negative effects on productivity and fruit quality, however, when the deficit lasted until the finals stages, besides the quality, the productivity fell about 22% for a water saving of up to 54%.…”
Section: Introductionmentioning
confidence: 83%
“…The success of RDI strongly depends on the appropriate use of microirrigation techniques, which allows the control of soil water content (Dichio et al, 2007). RDI has been used successfully maintaining yield and fruit quality in many fruit species (Ebel et al, 1995;Girona et al, 2003;Buendía et al, 2008;López et al, 2008), nut species Goldhamer and Beede, 2004;Romero et al, 2004;Girona et al, 2005) citrus species (Sánchez-Blanco et al, 1989;Castel and Buj, 1990;Domingo et al, 1996;Castel, 1999, 2000;Goldhamer and Salinas, 2000), wine grapes (Bravdo and Naor, 1996;McCarthy et al, 2002) and olives (Moriana et al, 2003).…”
Section: Introductionmentioning
confidence: 99%